Public awareness, attitude and knowledge of hepatitis B infection in North India - Singh, Vikramjeet; Mittal, Vineeta; Verma, Prashant; Sen, Manodeep; Das, Anupam; Singh, Peetam; Trivedi, Shalini (International Journal Of Community Medicine And Public Health, 2018)
Background: Information on attitudes towards hepatitis B vaccination, its coverage, and efficacy in general public is a major challenge for every country and should form the basis of health care policies. Therefore, it is important to assess the attitude and the coverage of the vaccination in public in India for further policy implementation as well as for their safety. The study objectives were to assess the knowledge of Hepatitis B and C in persons coming from community to attend a camp at tertiary care center, Lucknow and to correlate the level of awareness to the attitude they behold toward the disease. Methods: A comparative study of two years (2015 and 2017) using multiple choice structured questionnaires among 300 attendants (150 each year) coming to Gastro medicine outpatient department. The attendants assessed knowledge and awareness about hepatitis B and C infection, transmission, screening and vaccination was the tool of data collection. Results: Although most of the attendants were aware of the existence of hepatitis B and C infection, the level of awareness regarding the modes of transmission and vaccination was found to be dissatisfactory in 2015 attendants. A direct positive correlation as found between education level and awareness, which reveals that attendants with better knowledge and information had better attitudes toward the infection and prevention of hepatitis transmission. Conclusions: There is a still need to increase the level and quality of health education, vaccine accessibility and availability among people to prevent the spread of hepatitis B virus.